Postoperative Outcome of Laparoscopic Appendicectomy- A Study of 100 Cases - Rashid, Md Shoeb Ur; Begum, Muslema; Chhanda, Chhamita Sultana; Parveen, Farzana; Daud , AKM; Das, Aparna (Northern International Medical College Journal, 2022)
Background : An elegant, reliable procedure that can be easily performed is laparoscopic appendicectomy (LA). In patients with undiagnosed abdominal pain requiring more diagnostic investigations, as well as in patients with perforated appendicitis with or without intra-abdominal abscess, this procedure remain useful and safe. Objective : To evaluate the postoperative outcome and complication in laparoscopic appendicectomy. Methods : This prospective observational study was conducted at Rezia Taleb Hospital, Dhaka in Bangladesh. Total 100 cases were included in this study during the period of January 2018 to December 2019. Total 100 admitted uncomplicated acute appendicitis patients who underwent LA were enrolled in this study. Diagnosis is based on patient history (symptoms) and physical examination with an elevation of neutrophilic leukocytosis and raised CRP. In this study inclusion criteria of the cases were- Age <40 years, Alvarado Score 7 or more, Uncomplicated appendicitis, patients who underwent LA for appendicitis, both sexes. Exclusion criteria were - Incidental LA, patients with significant co-morbid medical conditions, patient unwilling to incorporate with the protocol, patients with psychiatric illness, and who lost to follow-up. Results : Out of 100 patients, most of them 63(63%) were in age group <20 years. The mean age was 21.70±6.21 years. Majority 77(77%) were male and 23(23%) were female and male: female ratio was 3.3:1. Among the 100 respondents, majority 95(95%) presented with migratory right iliac fossa pain and 5 (5%) had early postoperative complication. Majority 95(95%) patient’s pain control occurred within1-2 days with NSAID. Out of 95 Uncomplicated patients; Length of Hospital stay was 1-2 days in 90(94.7%) and 3-4 days in 5(5.3%) cases. Conclusion : This study showed that laparoscopic appendicectomy had found to be associated with shorter hospital stay, decreased postoperative pain and wound infection. Northern International Medical College Journal Vol. 12 No.1 July 2020, Page 486-488